2017
DOI: 10.1002/pola.28579
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly(β‐amino ester) gels in alcohols through transesterification: Method to conjugate drugs to polymer matrices

Abstract: Poly(β amino ester) polymers have received growing attention in the literature, owing to their ease of synthesis, versatile co-monomer selection, and highly tunable degradation kinetics. As such, they have shown extensive potential in many biomedical applications as well. In this work, it is demonstrated for the first time that PβAE polymers containing primary and secondary amine groups can undergo degradation by primary alcohols via transesterification mechanism. While this work emphasizes an important aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…According to these results, we can say that networks degrade via hydrolysis of the multiple ester groups on the backbone into small molecule diols, bis(-amino acids) and poly(acrylic acid) kinetic chains as reported in the literature [22,25,56].…”
Section: Degradation Of Networksupporting
confidence: 56%
“…According to these results, we can say that networks degrade via hydrolysis of the multiple ester groups on the backbone into small molecule diols, bis(-amino acids) and poly(acrylic acid) kinetic chains as reported in the literature [22,25,56].…”
Section: Degradation Of Networksupporting
confidence: 56%
“…Suarez et al’s research suggested the potential use of Ace-DEX MPs for controlled cargo delivery. Although other acid-labile carriers prepared from poly(β-amino) esters (PBAEs), poly(ortho esters) (POEs), or polyketals have also demonstrated some flexibility in degradation kinetics [3537], it is achieved mostly by varying polymer composition, which may result in complex manufacturing procedure and increased risk of adverse side effects associated with combining multiple biomaterials for controlled delivery [38]. These vehicles are also associated with other concerns: PBAEs may lead to severe side effects for long-term treatment due to potential toxicity [39, 40]; POEs are only stable under basic conditions and hydrolyze quickly in both acidic and neutral environments [41]; and, polyketals are synthesized via complex reactions, resulting in high manufacturing cost and limited accessibility [42].…”
Section: Introductionmentioning
confidence: 99%
“…By controlling MP CAC or polymer molecular weight, degradation half-lives can range from hours to months. Despite some flexibility in degradation kinetics of delivery vehicles formulated using other acid-sensitive polymers, such as poly(β-amino) esters (PBAEs), poly(ortho esters) (POEs), or polyketals, modulating degradation half-lives is achieved mostly through less straightforward chemical modifications or using polymer blends [3436].…”
Section: Introductionmentioning
confidence: 99%